Oral health-related quality of life and parental anxiety in chinese children undergoing Dental General Anesthesia: a prospective study - Ce Gou; Yan Wang; Ran Yang; Ruijie Huang; Qiong Zhang; Jing Zou (BMC, 2021)
Abstract Dental general anesthesia (DGA) is an effective treatment for very young children or those who have severe dental fear and mental or physical disabilities. However, the long-term impacts of DGA on oral health-related quality of life (OHRQoL) and parents' anxiety in China are still questionable. This study aimed to assess the influence of DGA on OHRQoL in Chinese children and their parents' psychological status. A total of 204 children and their parents participated in this study. The ECOHIS was applied to evaluate OHRQoL in children. The parents' anxiety was analyzed using the Chinese version of the Kessler 10 scale. The internal consistency was evaluated with Cronbach's alpha coefficient, and Wilcoxon signed-rank test was used for statistical analyses. The scores of each section of ECOHIS decreased one month after the procedure except for the self-image and social sections (P < 0.05). The scores of the Kessler 10 scale decreased one month after DGA and kept decreasing six months later (P < 0.05). The parents' Kessler 10 scores exhibited a moderately positive correlation with the children's ECOHIS scores (r = 0.480, P < 0.05). After DGA, the OHRQoL of Chinese children and their parents' mental health continued to improve. And they exhibited positive correlation.